Guía informativa y turística sobre los cinco patrimonios de Alausi - Mancero Niama, Esteban Alexis (2013)
Within the document was a complete collection and theoretical analysis on three basic axes which have governed this final thesis, the terms to which they are referring is, communication, identity and culture. These three sections of study have been worked independently, and has given them a special tratativa, to meet the needs that were presented at work, in order to obtain an indefatigable academic support, which contribute arguments in conducting and layout of the Guide.